Climate-Determined Suitability of the Water Saving Technology "Alternate Wetting and Drying" in Rice Systems: A Scalable Methodology demonstrated for a Province in the Philippines - Nelson, Andrew; Wassmann, Reiner; Sander, Björn Ole; Palao, Leo K. (Public Library of Science, 2015)
70% of the world’s freshwater is used for irrigated agriculture and demand is expected to increase to meet future food security requirements. In Asia, rice accounts for the largest proportion of irrigated water use and reducing or conserving water in rice systems has been a long standing goal in agricultural research. The Alternate Wetting and Drying (AWD) technique has been developed to reduce water use by up to 30% compared to the continuously flooded conditions typically found in rice systems, while not impacting yield. AWD also reduces methane emissions produced by anaerobic archae and hence has applications for reducing water use and greenhouse gas emissions. Although AWD is being promoted across Asia, there have been no attempts to estimate the suitable area for this promising technology on a large scale. We present and demonstrate a spatial and temporal climate suitability assessment method for AWD that can be widely applied across rice systems in Asia. We use a simple water balance model and easily available spatial and temporal information on rice area, rice seasonality, rainfall, potential evapotranspiration and soil percolation rates to assess the suitable area per season. We apply the model to Cagayan province in the Philippines and conduct a sensitivity analysis to account for uncertainties in soil percolation and suitability classification. As expected, the entire dry season is climatically suitable for AWD for all scenarios. A further 60% of the wet season area is found suitable contradicting general perceptions that AWD would not be feasible in the wet season and showing that spatial and temporal assessments are necessary to explore the full potential of AWD.